Web of Thing Application for Monitoring Precision Agriculture Using Wireless Sensor Network - Nurul Fahmi; Eko Prayitno; Siti Fitriani (JURNAL INFOTEL, 2019)
Wireless Sensor Network (WSN) is a technology which can help humans solve problems in daily life for monitoring the environment. This can be done to help farmers in monitoring and making decisions for watering plants. In this study, temperature, humidity and soil moisture sensors were used to help farmers monitor web-based precision agriculture, and the system which be built could make a decision to automatically water plants based on soil conditions. The results of measuring precision agriculture from the sensor node will be sent to the gateway using Zigbee 802.15.4. The data will be stored in the MySQL database provided by the gateway. Then it will be synchronized to the cloud using IoT technology, so users can access it in real time by using web-based application. From the system which is developed, it really helps farmers to complete their work and make innovation in the digital era.